Alterations in protein N-glycosylation confer vanadate resistance in Ogataea polymorpha mutants defective in phosphomannosylation - Pakhomova, Maria; Karginov, Azamat; Kulakova, Maria; Vladimirova, Polina; Mitkevich, Olga; Agaphonov, Michael (Frontiers in Molecular Biosciences, 2026)
Different yeast species, including Ogataea polymorpha, are often used as hosts for recombinant protein production. One of the most important factors limiting such applications is yeast-specific modifications of glycoside chains attached to secretory proteins. This problem can potentially be solved by the identification and inactivation of genes responsible for these modifications. Previously we demonstrated that the exceptional resistance of O. polymorpha to vanadate depends on the ABV1 gene responsible for the mannosylphosphorylation of protein glycoside chain in the Golgi apparatus. Here we show that mutations altering protein glycosylation in the secretory pathway can be selected in the abv1Δ mutant by screening for vanadate resistance. For one such mutant, we identified the responsible gene, which encodes a putative α-1,2-mannosyltransferase. To ensure the absence of phosphomannosylation, both O. polymorpha genes, ABV1 and MNN4, which encode mannosylphosphate transferase homologs, were inactivated. Some vanadate resistant mutants generated in this strain showed defects in N-glycosylation of a recombinant glycoprotein. This demonstrates that the effects of N-glycosylation on vanadate resistance in O. polymorpha are not mediated by phosphomannosylation per se and that identification of certain genes responsible for N-glycosylation in this yeast can be performed via selection of vanadate resistant clones.